2021
DOI: 10.3389/fcvm.2021.751421
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences and Postoperative Delirium in Adult Patients Undergoing Cardiac Valve Surgery

Abstract: Background: Postoperative delirium (POD) is common in patients following cardiac surgery. According to studies on non-cardiac surgery, males suffered from higher incidence of POD. However, there is no report about effect of gender differences on POD occurrence in cardiac surgery patients. The aim of this study was to investigate the effect of gender differences on POD occurrence in adult patients after cardiac valve surgery.Methods: This is a retrospective case-control study. We recorded the clinical data in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
3
15
1
2
Order By: Relevance
“…Men tended to develop a delirium more often than women, as we already observed at aortic surgery [ 26 ]. This is in line with the findings of Wang et al that male gender is an important predictor for postoperative delirium following cardiac surgery [ 27 ]. Moreover, red blood cell transfusion, which was more frequent in our male patients postoperatively, was shown to be an important initiating risk factor for delirium after cardiac surgery in a review by Koster et al [ 28 ], as well as the association with prolonged postoperative stay in our male patients [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Men tended to develop a delirium more often than women, as we already observed at aortic surgery [ 26 ]. This is in line with the findings of Wang et al that male gender is an important predictor for postoperative delirium following cardiac surgery [ 27 ]. Moreover, red blood cell transfusion, which was more frequent in our male patients postoperatively, was shown to be an important initiating risk factor for delirium after cardiac surgery in a review by Koster et al [ 28 ], as well as the association with prolonged postoperative stay in our male patients [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…In terms of gender distribution, it appears that males (38%) in the total cohort were substantially more likely to have been delirious than females (21%). These findings are supported by the 2021 retrospective study of cardiac surgery patients by Wang et al [ 15 ]. There, male gender was confirmed as a significant risk factor for delirium development.…”
Section: Discussionsupporting
confidence: 67%
“…Less discussed were gender differences in relation to POD development. One study showed, based on adjusted regression results, that male sex is an important risk factor for delirium development during cardiac valve surgery [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…27 Our finding may be a result of differences in patient demographics between LEB and hip fracture patients, differences in screening practices, and inclusion of hypoactive delirium in our study, which is more common in female patients. 28 Using the 11-item mFI score, frailty was not an independent predictor of POD. On bivariate analysis, frailty was associated with POD; after accounting for age, this association did not persist.…”
Section: Discussionmentioning
confidence: 92%